Chloral Hydrate Alters Brain Activation Induced by Methamphetamine-Associated Cue and Prevents Relapse - Jiang, Chenyu; Xu, Yunlong; Zhong, Jiafeng; Wu, Junyan; He, Jian; Xu, Wei; Zhu, Yingjie (Frontiers in Molecular Neuroscience, 2022)
Methamphetamine is a highly addictive drug and its abuse leads to serious health and social problems. Until now, no effective medications are yet available for the treatment of methamphetamine addiction. Our study reveals that chloral hydrate, a clinical sedative drug, suppresses the seeking desire for methamphetamine. After 5 days of continuous administration (subanesthetic dose 50 mg/kg and 100 mg/kg), methamphetamine-seeking behavior of rats was inhibited in the condition place preference and intravenous self-administration tests. Furthermore, chloral hydrate treatment robustly suppressed cue-induced methamphetamine relapse. The whole brain c-fos immunostaining revealed that chloral hydrate treatment suppressed neuronal activity in the rhomboid thalamic nucleus (Rh), dorsal endopiriform nucleus (dEn), and claustrum (Cl) while enhanced zona incerta (ZI) activity during cue-induced methamphetamine relapse. Therefore, chloral hydrate could remodel neural network activity and serve as a potential medicine to treat methamphetamine addiction.